Strategic Management of Non Profit Organization to Increase the Existence of Al-Mutmainnah Ponorogo Islamic Boarding School - Yuli Umro’atin; Agus Zainul Fitri (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2023)
Islamic educational institutions must carry out strategic management to formulate strategic plans and according to needs in order to achieve educational goals. The existence of the community can provide opportunities as well as threats to the sustainability of Islamic educational institutions. The goals of this research are (1) to study and develop a new theory about strategic planning to increase the exsistence of Religious Boarding School Al-Mutmainnah, (2) to study and develop new theories about the implementation of strategies, and (3) to study and develop a new theory on strategy evaluation.. The research method is qualitative research with a case study approach, data collection techniques through in depth interviews, participant observation, and documentation. Research results: Strategic planning at Religious Boarding School Al-Mutmainnah Winong Jetis Ponorogo, by holding joint meetings in the formulation of educational vision, mission, and goals, determining organizational structure, and preparing short and medium-term programs, as well as operational financing budgets are also determined based on management policies, foundations and principals. Implementation of strategies in managing Religious Boarding Scholl Al-Mutmainnah by controlling the administration of the institution, implementing a fundraising system from the community or donors, incentives for the village government and the Ministry of Religion, free tuition fees, and inviting the community, especially the guardians of students to participate in education. The evaluation of the strategy, was conducted by the head of the Islamic school together with the foundation's management by monitors the strategic plan, and attends a joint meeting with the Diniyah Takmiliyah Coordination Forum throughout the Jetis sub district of Ponorogo city.